Changes in Healthy Childhood Lifestyle Behaviors in Japanese Rural Areas. (15th March 2013) - Nakano, Takahiro; Kasuga, Kosho; Murase, Tomohiko; Suzuki, Kazuhiro
ABSTRACT: BACKGROUND: Unhealthy lifestyles during childhood constitute a public health problem in Japan. However, current health education in Japan is ineffective in counteracting them. Previous studies contend that healthy lifestyles in children vary by academic grade and sex. This study examined changes throughout childhood suggests some intervention points for lifestyle education. METHODS: The participants were 2833 elementary and junior high school students living in Japanese rural areas. Data on 26 variables assigned to 5 subfactors were collected. We estimated the composite score of each subfactor on the basis of item response theory. A 2‐way ANOVA and a graph review were performed to explore the differences and changes by sex and grade. RESULTS: Most of the main effects for sex and grade were statistically significant. Lifestyle behaviors acquired early in elementary school were lost as students progressed to higher grades. CONCLUSIONS: The research indicated the following emphases: (1) Physical activity and leisure habits should be focused on girls and hygiene habits on boys; (2) Continuous education for a healthy lifestyle is essential to maintain good health among children; (3) Education for healthy lifestyle can be classified into 2 important stages such as for dietary and sleeping habits, education from the upper grades of elementary school is important, whereas for other routine activities, reeducation in junior high school is effective.